Tradisi Popas Lipu Kesultanan Bacan di Kecamatan Bacan Kab Halmahera Selatan: Studi Living Qur’an - Irfan; Achmad Dardirie; Ujaifa Aden (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The implementation of a tradition that has been practiced, maintained, and preserved for generations by ancestors often receives comments and criticism from certain parties, because in its implementation, sometimes the strong basis or arguments for carrying out the tradition are not known, as well as what readings and virtues are believed to be derived from the readings in the implementation. To gather accurate information for this research, the researcher formulated several questions, namely: How is the Popas Lipu tradition practiced by the Bacan Sultanate in Amasing Kota Village, Bacan District? What is the basis for the implementation of the Popas Lipu tradition by the Bacan Sultanate in Amasing Kota Village, Bacan District? How do people perceive the verses recited in the implementation of the Popas Lipu tradition by the Bacan Sultanate in Amasing Kota Village, Bacan District? The research method used in this study was descriptive qualitative, with data collection techniques including observation, interviews, and documentation, and analysis techniques including processing, presenting, and drawing conclusions. The findings of this study show that the Popas Lipu tradition is carried out by tawaf or circling the village and stopping at several points to recite prayers for protection. Second, the basis for the implementation of the popas lipu tradition is verses from the Qur'an and hadiths of the Prophet Muhammad. Third, the community believes that the implementation of the popas lipu tradition will bring power from Allah SWT through the verses and prayers recited so that the land of Bacan will be protected and spared from disasters, calamities, epidemics, and other diseases.